Penanganan Pengungsi Luar Negeri Menurut Peraturan Presiden Nomor 125 Tahun 2016 Ditinjau dari Perspektif Fiqh Siyasah - Fawwaz Fawwaz; Mumtazinur Mumtazinur (Law Department, Sharia and Law Faculty., 2021)
The shelter for Rohingya refugees who were declared officially as refugees was initially rejected by the Lhokseumawe City Government, but pressure from the community made the Government finally accept the arrival of Rohingya refugees, this acceptance demanded the Lhokseumawe City Government to implement Presidential Regulation No. The formulation of the problem is first, how the form of handling given to Rohingya refugees in Lhokseumawe is reviewed according to Presidential Decree No. 125 of 2016. Second, how is the form of handling Rohingya refugees in Lhokseumawe reviewed according to fiqh siyasah. This study uses an empirical normative legal approach, using field research and library research, namely examining written law as well as facts in the field using descriptive analytical patterns to describe or provide an overview of the object under study through data or samples collected. have been collected by drawing conclusions. From the results of the study, it was found that the handling of refugees has been carried out by the Lhokseumawe City Government, namely in the form of rescue, security, shelter, and health checks for refugees, and if viewed from the fiqh siyasah their rights have also been fulfilled, especially the right to protect life, safeguard property. , worship, and a decent place to live. So it can be concluded that the handling of Rohingya refugees is in accordance with Presidential Regulation No. 125 of 2016 and fiqh siyasa through the fulfillment of the rights of refugees by saving lives and providing shelter for Rohingya refugees.